Did Paul Get Luther Right? - Brondos, David A. (Dialog, 2007)
Did Paul and Luther proclaim the same gospel? Although Luther's understanding of the work of Christ and his idea of the “joyous exchange” between Christ and believers reflect many ideas that are foreign to Paul's thought, both agree on the heart of the gospel, namely, that justification is by faith alone, since “faith alone fulfills the law.” In Christ God graciously accepts sinners just as they are, so that as they live out of faith, trusting solely in God for forgiveness and new life, they may become the righteous people God desires that they be, not for God's sake, but for the sake of human beings themselves.